2016
DOI: 10.1007/s10195-016-0405-z
|View full text |Cite
|
Sign up to set email alerts
|

Long versus short cephalomedullary nail for trochanteric femur fractures (OTA 31-A1, A2 and A3): a systematic review

Abstract: BackgroundBoth long and short cephalomedullary nails (CMN) may be used to treat trochanteric femur fractures. The objective of this paper was to compare the clinical outcomes between long and short CMN in the treatment of trochanteric hip fractures.Materials and methodsA literature search was performed, identifying 135 papers; 4 of which met inclusion and exclusion criteria. Papers included were those that compared cohorts of long and short nails for stable trochanteric femur fractures of level III evidence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 28 publications
(39 reference statements)
4
56
0
Order By: Relevance
“…But, Dunn (2016), reported the amount of received blood in the short nail group was 8.8% (39 ml) which was lower than that of the long nail group and thus both the groups were seen to be statistically differentiated from each other. We found the duration of surgery in the short PFN group was signif icantly lower than the PFN group which supports the result of Dunn (2016). In our study, the mean duration of the union in the long PFN group was shorter than the short PFN group, but the differences were not statistically signif icant.…”
Section: Abstract Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…But, Dunn (2016), reported the amount of received blood in the short nail group was 8.8% (39 ml) which was lower than that of the long nail group and thus both the groups were seen to be statistically differentiated from each other. We found the duration of surgery in the short PFN group was signif icantly lower than the PFN group which supports the result of Dunn (2016). In our study, the mean duration of the union in the long PFN group was shorter than the short PFN group, but the differences were not statistically signif icant.…”
Section: Abstract Introductionsupporting
confidence: 84%
“…Although the difference in therapeutic results from short and long PFNs is not explicitly stated, some studies have highlighted the cost of using long PFN, the surgical time, the amount of bleeding during surgery and its complications more than the short PFN. Also, the results of studies have shown that the use of long PFN does not reduce the chances of Periprosthetic fracture and reoperation (Dunn et al, 2016;Kanakaris ., 2015;Boone ., 2014;Kleweno ., 2014). In contrast to some studies, there was no signif icant difference between the clinical outcomes of the two methods, and both methods were useful in treating intertrochanteric fractures (Kleweno ., 2014;Vaughn , 2015;Okcu ., 2013).…”
Section: Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang [ 22 ] and Li [ 31 ] noted that the use of long PFNA nails in patients improved the clinical outcomes compared to short nails especially failure rates and pain. Other authors that have looked at long and short PFNA nails and found no difference in clinical outcomes except for intraoperative outcomes such as operating time and blood loss which favour the smaller nails [ 32 34 ]. Although our meta-analysis found significant differences in clinical outcomes between InterTAN and PFNA, we cannot be certain that nail dimension did not contribute to the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing between long or short nails during internal xation for intertrochanteric fractures in the elderly is still controversial. In 2016, John et al [8] . reported that short nails had a lower reoperation rate than long nails, and that short nails were associated with a shorter operation time, , less intraoperative blood loss, and lower hospitalization costs.…”
Section: Discussionmentioning
confidence: 99%